2021
DOI: 10.1101/2021.06.16.21258972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early but not late convalescent plasma is associated with better survival in moderate-to-severe COVID-19

Abstract: Background: Limited therapeutic options exist for coronavirus disease 2019 (COVID-19). COVID-19 convalescent plasma (CCP) is a potential therapeutic, but there is limited data for patients with moderate-to-severe disease. Research Question: What are outcomes associated with administration of CCP in patients with moderate-to-severe COVID-19 infection? Study Design and Methods: We conducted a propensity score-matched analysis of patients with moderate-to-severe COVID-19. The primary endpoints were in-hospital m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(32 reference statements)
0
13
0
1
Order By: Relevance
“…This study showed that the time to negative PCR was 14 days in CCP‐treated patients versus 9.5 days in 59 historical controls 54 . Unfortunately, most PSM studies did not assess this parameter at all 55‐66 . Yoon et al 57 found a correlation between anti‐Spike IgG titre and PCR Ct in CCP recipients, but antibody levels were not measured in matched controls.…”
Section: Resultsmentioning
confidence: 84%
“…This study showed that the time to negative PCR was 14 days in CCP‐treated patients versus 9.5 days in 59 historical controls 54 . Unfortunately, most PSM studies did not assess this parameter at all 55‐66 . Yoon et al 57 found a correlation between anti‐Spike IgG titre and PCR Ct in CCP recipients, but antibody levels were not measured in matched controls.…”
Section: Resultsmentioning
confidence: 84%
“…We found an earlier administration of CPT is associated with better odds for favorable outcomes. Similarly, a number of recent studies 17 , 18 also echoed that while early application of CPT is beneficial in critically ill COVID-19 patients, late CPT is futile. However, another recent RCT reported no significant reduction of mortality rate (OR 3.04, 95% CI 0.54–17.2, p = 0.25), and the requirement for mechanical ventilation (OR 3.04, 95% CI 0.54–17.2, p = 0.25) is associated with early administration of CPT in comparison with the deferred patients.…”
Section: Resultsmentioning
confidence: 98%
“…Of interest, a retrospective PSM study from Providence did not show any benefit, but patients were treated at a median of 7 days after onset of symptoms (67). Another PSM study from Yale associated CCP with a 35% reduction in mortality (68). That study is notable in that it included patients on mechanical ventilation who would not normally be expected to benefit from CCP and the percentage of individuals receiving corticosteroids was very low since the study was conducted in the early days of the pandemic in the USA.…”
Section: Resultsmentioning
confidence: 99%